Sustainable integrated oil-palm livestock practice to enhance soil organic matter and carbon sequestration potential - Umar, Y.; Sayed, K.; Syakir, M. I.; Al-Saedi, T. K.; Azhar, B.; Tohiran, K. A.; Nobilly, F. (Springer Nature, 2025)
Present study investigates the impacts of sustainable integrated crop-livestock-oil-palm (ICL) operations on soil characteristics and capability for soil amendments (carbon sequestration). This study employed the zigzag method to examine soil samples obtained from three different management systems i.e. conventional herbicide weed control management (HM); free-range cattle grazing weed management (FRCM); and systematic rotational cattle grazing weed management (SRCM). The equivalent soil mass and fixed-depth techniques were used to calculate soil organic carbon (SOC) stocks. The management systems HM, FRCM, and SRCM exhibited varying SOC stocks averaged values, with 31.35, 40.96, and 46.88 t/ha, respectively. Likewise, HM, FRCM, and SRCM the correlation between C:N ratio, indicating a positive correlation with an R-squared value 0.8522, 0.5336, 0.1003 (P values of 0.9232, 0.7305, 0.3167), respectively. The results revealed significant variations in organic carbon (OC), total nitrogen (TN), and total phosphorous (TP) levels among the management systems, indicating the influence of weed management practices. Hence, P-values for OC, TN, and TP are P < 0.0001, P < 0.0001, and P < 0.0001, respectively. The analysis revealed a notable difference in soil organic matter (SOM) among management systems (P < 0.0001). Specifically, SRCM approaches demonstrated higher levels of SOC, TN, TP, and SOM compared to conventional practices. Additionally, there are differences in soil bulk density (BD) and pH among management systems. Overall, ICL technique using the SRCM system has produced the highest levels of enhanced soil characteristics and carbon sequestration in the form of SOC.